Organic Solvent Nanofiltration (OSN): A New Technology Platform for Liquid-Phase Oligonucleotide Synthesis (LPOS) - Kim,JF; Gaffney,PRJ; Valtcheva,IB; Williams,G; Buswell,AM; Anson,MS; Livingston,AG (Organic Process Research and Development, 2016)
Organic solvent nanofiltration (OSN) technology is a membrane process for molecular separation in harsh organic media. However, despite having well-documented potential applications, development hurdles have hindered the widespread uptake of OSN technology. One of the most promising areas of application is as an iterative synthesis platform, for instance for oligonucleotides or peptides, where a thorough purification step is required after each synthesis cycle, preferably in the same working solvent. In this work, we report a process development study for liquid-phase oligonucleotide synthesis (LPOS) using OSN technology. Oligonucleotide (oligo) based drugs are being advanced as a new generation of therapeutics functioning at the protein expression level. Currently, over 100 oligo based drugs are undergoing clinical trials, suggesting that it will soon be necessary to produce oligos at a scale of metric tons per year. However, there are as yet no synthesis platforms that can manufacture oligos at >10 kg batch scale. With the process developed here, we have successfully carried out eight iterative cycles of chain extension and synthesized 5-mer and 9-mer 2′-O-methyl oligoribonucleotide phosphorothioates, all in liquid phase media. This paper discusses the key challenges, both anticipated and unexpected, faced during development of this process and suggests solutions to reduce the development period. An economic analysis has been carried out, highlighting the potential competitiveness of the LPOS-OSN process and the necessity for a solvent recovery unit.